Sejarah Penulisan dan Pembukuan Hadith: Satu Sorotan - Abd. Rahman, Mohd. Muhiden (Jurnal Usuluddin, 2004)
Al-Hadith as the second source of Islamic Law has its own history particularly related to its writing and recording. This paper attempts to elaborate that hadiths were not created or invented in the later period of Islam. There were three stages or periods of writing and recording of hadiths: the Prophet, the companions and the period of the followers. During the periods of the Prophet and his companions, not all hadiths were written and recorded systematically for memorization was much preferred. The writing and recording of hadiths was in its magnificient period during the days of the followers particularly in the fourth century of Hijrah which witnessed the emergence of books and hadith experts.